Extraction of Lanthanum and Cerıum from a Bastnasite Ore By Direct Acidic Leaching - Kursunoglu, Sait; Top, S.; Hussaini, Shokrullah; Gokcen, H. S.; Altiner, Mahmut; Ozsarac, Safak; Kaya, Muammer (Chamber of Mining Engineers of Turkey, 2020)
The extraction of lanthanum (La) and cerium (Ce) from a bastnasite ore by direct acidic leaching was investigated. The effects of acid concentration and leaching temperature on the extraction of La and Ce from the ore were tested. Using nitric (NHO3), more than 85% of the La and Ce were simultaneously extracted into leach solution whereas the La and Ce dissolutions were determined as less than 85% by using sulfuric acid (H2SO4). The La dissolution exceeded 90% by using hydrochloric acid (HCl); however, the Ce dissolution remained below 85% under the following conditions: solid-to-liquid ratio of 20% (w/v), the acid concentration of 20%, leaching temperature of 25°C and leaching time of 1 h. The result revealed that HNO3 could be used as a solvent for the maximum simultaneous extraction of the La and Ce from the bastnasite ore. The leaching temperature had no crucial effect on the dissolution of La and Ce when HNO3 or HCl solutions were preferred as a solvating agent. However, the leaching temperature had a slight positive effect on the dissolutions of La and Ce when H2SO4 was used as a solvent. © 2023 Elsevier B.V., All rights reserved.
Direkt Asit Liçi ile Bastnazit Cevherinden Lantanyum ve Seryum Kazanımı
Keywords: Bastnasite Ore; Cerium; Direct Acidic Leaching; Lanthanum; Cerium; Chlorine Compounds; Extraction; Hydrochloric Acid; Lanthanum; Leaching; Ores; Acid Concentrations; Acid Leaching; Acidic Leaching; Bastnasite; Bastnasite Ore; Condition; Direct Acidic Leaching; Effect of Acids; Lanthanum (La); Leach Solutions; Dissolution; Kimya, Analitik; Maden İşletme Ve Cevher Hazırlama